GAMBARAN PERTUMBUHAN DAN PERKEMBANGAN BALITA PEDAGANG PASAR DWIKORA PARLUASAN DI KOTA PEMATANG SIANTAR TAHUN 2012 - Romilly Purba (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Children under five years is as the golden period and as good time to make optimal growth. The growth of children under five years of traditional sellers in Dwikora Parluasan market was frequently neglected because their parents seldom took their children to Integrated Health Care Unit. This research is intended to describe the growth and development of the children in Dwikora market Pematang Siantar city in 2012. This was descriptive research using cross sectional design. Sample taken was done with purposive sampling. The criteria was with the permission of the parents. The results of research showed that the growth of the children based on the weight for height index in Dwikora market Pematang Siantar city in 2012 was mostly normal. However, some babies were thin, very thin, fat and very fat. The growth based on the weight for age index, mostly were normal even though some with less weight and with problem in their growth. The growth based on the height for age and weight for age were mostly normal. However, some children were short and very short. The development of the children in Dwikora market was good even though some with problem compared to other normal children. Based on the results of research, it is suggested to health providers to give counseling and guidance regarding the importance of the growth and development of the children. The availability of Integrated Health Care Unit is expected in Dwikora market such as what can be found in Horas market Pematang Siantar. Key words : Growth, Development, Children Under Five Years of Traditional Sellers